Financial technology dalam koperasi : Dimensi sosio ekonomi dan dimensi kinerja yang diharapkan (performance expectancy) nasabah - Amos, Viktor; Pahlevi, Cepi; Rahim, Fauzi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research aims to analyze the socio-economic dimensions and performance expectations that affect customers using cooperative fintech. This research was carried out at Credit Union Mekar Kasih, which already uses fintech and serves a wide area in South and West Sulawesi. The sample amounted to 200 respondents with a simple random sampling technique. Data collection did by survey method. Data were analyzed using PLSStructural Equation Modeling (SEM). The results show that the socio-economic dimensions that affect customers using fintech in cooperatives are revenue, occupation, space or distance of the customer's domicile with financial institutions, and education. The socio-economic dimension can be shortened to ROSE. The dimensions of performance expectancy that affect the use of fintech include cost efficiency (cost efficiency), residual income (residual income), ability to disburse loans/liquidity (ability to disburse loans), time efficiency, and environmentally friendly/paperless). The performance dimension of customer expectations is abbreviated to CRATE. The use of fintech is seen based on transaction traffic, the number of users, and changes in the structure of outstanding loansand bad loans.